Taggar Wood and its Indian Substitute - Ghosh, S. S.; Shahi, R. (Indian Forester, 1961)
An altogether new scented wood of India sold under the name "Taggar wood" has been found to be Hemicyclia porteri Gamble. Its anatomical and other characteristics have been described in detail. Distinguishing features of this and other well-known scented woods of the world have also been discussed together with the description of the genuine taggar wood (Cinnamosma fragrans Baill.) of Madagascar to facilitate their easy determination.